Digitalising Religious Practice: Community Engagement in Qurban Rituals at Masjid Jogokariyan - Zerin Amalina (BELIEF: Sociology of Religion Journal, 2025)
The development of modern technology has brought significant changes in the implementation of religious community worship. The challenge is how mosques, as religious institutions, can respond to this transformation without compromising the core values of their teachings. This study examines how mosques influence community involvement in qurbani worship and how mosques manage these activities in a modern context while still benefiting the community. The purpose of this study is to analyze the form of digitalization applied and its impact on the participation of the ummah in the implementation of qurbani worship. The method employed is field research, with observation as the data-collection technique. The results of this study show that digitalization, such as online registration, qurbani management information systems, and real-time reporting, has increased transparency, trust, and community involvement in the implementation of qurbani worship. Thus, the digitalization implemented at the Jogokariyan mosque strengthens religious community engagement and underscores the mosque's role as a public service grounded in religious values, adapted to contemporary contexts.